KRITIK ISLAM ATAS TEORI EVOLUSI DARWIN (SUATU KAJIAN TENTANG ASAL-USUL KEHIDUPAN MANUSIA) (Institut Agama Islam Negeri (IAIN) Palu, 2006)
Since its launching for the first time in 1859, Darwinâs evolutionary theory never freed from critiques, particularly that from theologians. However, since the theory is deemed as being scientific while belief in religion is unscientific, most ofÂ scientists and educatorsÂ Â support the misleading theory. Darwin has placed humans in the lowest position in their creatures, since according to him, the process of creating humansÂ is through several phases, from the lowest phaseÂ to the perfection phase of their creatures in order to be survival. It is what he calls an evolution.Â Kata Kunci: Islam, evolusi, manusia